Effect of Fourier transform on the streaming in quantum lattice gas algorithms. Issue 3 (3rd April 2018) - Oganesov, Armen; Vahala, George; Vahala, Linda; Soe, Min
ABSTRACT: All our previous quantum lattice gas algorithms for nonlinear physics have approximated the kinetic energy operator by streaming sequences to neighboring lattice sites. Here, the kinetic energy can be treated to all orders by Fourier transforming the kinetic energy operator with interlaced Dirac-based unitary collision operators. Benchmarking against exact solutions for the 1D nonlinear Schrodinger equation shows an extended range of parameters (soliton speeds and amplitudes) over the Dirac-based near-lattice-site streaming quantum algorithm.